The Effect of Giving Discounts and Service Quality on Sales at PT Midi Utama Indonesia Tbk Alfamidi Branch of SM Raja 4 Medan - Nikita Ulandari; Risa Kartika Lubis (SEAN Institute, 2021)
This study aims to determine how much the effect of discounting and service quality on sales of PT. Midi Utama Indonesia TBK Alfamidi branch Sm Raja 4 Medan. The data analysis technique used in this research is qualitative and quantitative analysis. The sample in this research, amounting to 50 people, namely the Consumer Alfamidi Sm Raja 4 Medan. The results of this study obtained the Multiple Regression equation Y = (2.535) + 0.166 X1 + 0.105 X2, where the constant coefficient (a) is 2.535, the regression coefficient value (X1) is 0.166 and the regression coefficient value (X2) is 0.105. The results of the validity test with a sample size of 50 and a value of rtabel 0.279., Of the 26 items, the lowest r table value was 0.285 but it was still declared valid because r table> rcount. And based on the results of the t hypothesis test on the effect of giving discounts on sales variables, the tcount value is obtained (10.553). And based on the results of the t hypothesis test on the effect of service quality on sales variables, it is obtained value_count (2.104). Because the value of t is greater than t table, the hypothesis is accepted. And based on the determination coefficient test (KD) or R Square (R2), it is known that the R Square value is 0.861 or 86.1%, while the remaining 13.9% is influenced by other variables not examined by this study. And based on the coefficient of determination test (KD) or Adjusted R Square (R2), it is known that the value of R Square is 0.854 or 85.4%, while the remaining 14.6% is influenced by other variables not examined by this study.